Transgene expression from CpG-reduced lentiviral gene delivery vectors in vitro - Low, Poh Tee; Lai, Mei I.; Ngai, Siew Ching; Abdullah, Syahrilnizam (Elsevier, 2014)
Current viral gene delivery vectors for gene therapy are inefficient due to short-lived transgene expression attributed to the cytosine-phosphate-guanine (CpG) motifs in the transgene. Here we assessed the effects of CpG motif reduction in lentiviral (LV) gene delivery context on the level and duration of reporter gene expression in Chinese Hamster Ovary (CHO) cells, Human Immortalized Myelogenous Leukemia (K562) cells and hematopoietic stem cells (HSCs). The cells were transduced with LV carrying Zero-CpG green fluorescent protein (ZGFP) reporter gene, LV/CMV/ZGFP. The GFP expression was compared to its non CpG-depleted GFP reporter gene LV (LV/CMV/GFP) counterpart. The LV/CMV/ZGFP exhibited prolonged transgene expression in CHO cells and HSCs up to 10 days and 14 days, in the respective cells. This effect was not seen in the transduced K562 cells, which may be due to the DNA hypomethylation status of the cancer cell line. Transgene copy number analysis verified that the GFP expression was not from pseudo-transduction and the transgene remained in the genome of the cells throughout the period of the study. The modest positive effects from the LV/CMV/ZGFP suggest that the reduction of CpG in the LV construct was not substantial to generate higher and more prolonged transgene expression.